"My name is Adrienne Clarkson and I have a complaint.that damn Circumpolar tour!" "Proceed!" "How would you like to navigate the far north stopping only to commune with the occasional walrus, [.] - Harrop, Graham (Globe and Mail, 2003)
"My name is Adrienne Clarkson and I have a complaint.that damn Circumpolar tour!" "Proceed!" "How would you like to navigate the far north stopping only to commune with the occasional walrus, narwhal or harp seal?" ".and the broken arm?" "I didn't get it playing bocce buddy boy!"